2022
DOI: 10.3390/ijerph19148742
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Experiences of Patients with Coronavirus Disease 2019 (COVID-19) during and after Hospitalization: A Descriptive Phenomenological Study

Abstract: During an infectious disease pandemic, patients may experience various psychological issues. Few studies have focused on survivors’ experiences in Hong Kong. This study aimed to assess the psychological impacts of coronavirus disease 2019 (COVID-19) on survivors during admission to and discharge from COVID-19 wards using a descriptive phenomenological design. Purposive sampling was used to recruit 20 participants aged 30–77 years recently discharged from an isolation ward at an acute care facility and transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…Qualitative studies have shown that several groups of individuals who experienced distress during the pandemic emerged from this experience feeling more liberated [47,[58][59][60][61][62][63][64][65][66][67][68]. These participant groups varied greatly in terms of demographics and contexts.…”
Section: Ivd Scientific Implicationsmentioning
confidence: 99%
“…Qualitative studies have shown that several groups of individuals who experienced distress during the pandemic emerged from this experience feeling more liberated [47,[58][59][60][61][62][63][64][65][66][67][68]. These participant groups varied greatly in terms of demographics and contexts.…”
Section: Ivd Scientific Implicationsmentioning
confidence: 99%
“…At the time of discharge, the physiological systems are impaired, physiological reserves are depleted, and the body cannot effectively avoid or mitigate health threats [ 8 ]. In this line, hospitalization can imply psycho-physiological effects at long term that have been reported in different populations [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the European region, geriatric population or concomitant diseases like diabetes, cardiovascular disease, chronic respiratory diseases, and cancer increase the COVID‐19 complications that ultimately leads to intensive care unit (ICU) admission as well as life‐threatening consequences 5–7 . This catastrophic situation caused various clinical complications that required special care, including medical care, psychological care, respiratory support, life support, and renal replacement therapy, leading to admission to the ICU 7–9 . A range of different classes of medications such as antimalarial (hydroxychloroquine), antiparasitic (ivermectin), antibiotic (azithromycin), antiretroviral (darunavir), immunosuppressant (tocilizumab), and interferon‐beta have been considered as therapeutic agents to minimize the mortality rate caused by acute respiratory syndrome, mechanical ventilation and complications of SARS‐Cov‐2 virus 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] This catastrophic situation caused various clinical complications that required special care, including medical care, psychological care, respiratory support, life support, and renal replacement therapy, leading to admission to the ICU. [7][8][9] A range of different classes of medications such as antimalarial (hydroxychloroquine), antiparasitic (ivermectin), antibiotic (azithromycin), antiretroviral (darunavir), immunosuppressant (tocilizumab), and interferon-beta have been considered as therapeutic agents to minimize the mortality rate caused by acute respiratory syndrome, mechanical ventilation and complications of SARS-Cov-2 virus. 10,11 The National Health Service (NHS) of the United Kingdom presently recommends a neutralizing monoclonal antibody (sotrovimab) with some antiviral drugs namely nirmatrelvir, ritonavir, remdesivir, and molnupiravir for the treatment of COVID-19 affected people who are at the highest risk of getting critically ill. 12 Among them, remdesivir is US Food and Drug Administration-approved.…”
Section: Introductionmentioning
confidence: 99%